Water scarcity will constrain the formation of a world-class megalopolis in North China - Zhang, Zhuoying; Shi, Minjun; Chen, Kevin Z.; Yang, Hong; Wang, Shouyang (Nature Publishing Group, 2021)
The formation of world-class megalopolises has been a goal of urban development agencies around the world owing to their economic advantages. On their bids of becoming a world-class megalopolis, water availability is a factor that requires consideration. China has set an ambitious goal of developing a world-class megalopolis in the water-scarce Beijing-Tianjin-Hebei (BTH) region. This study investigates the water challenge the BTH region faces and the effects of main water conservation measures in the region towards the goal. An inter-city input–output model was constructed for identifying the water gap in the region and analyzing the effectiveness of main water conservation measures under various scenarios. The results indicate a significant gap between the water required to achieve the goal of becoming a world-class megalopolis and the region’s available water resources. Although proposed water conservation measures of improving water use efficiency and reducing agricultural water use provide a modest improvement, the amount of water required for urban development still exceeds the availability. The study emphasizes the significance of agricultural water use reduction in Hebei through crop system replacement from water-intensive winter wheat to water-saving crops. The study also proposes an alternative option of adjusting the development plan through redefining the boundary of the BTH megalopolis by excluding part of cities in Hebei. The results of this study contribute to a better understanding of the effect of water scarcity on urban development and thus provide references for other water-scarce regions with ambitious urban development goals.